La promesa de la sociología latinoamericana: La ciencia social a contruir - Germaná, César (2005)
The world where we live is following a process of deep mutations that form a new social order. Therefore, latin american sociology needs to construct a new image of the society, because the one that it had is now obsolete in substantial aspects. For that reason it needs to reorganize its theories, concepts and analysis methods. As A. Touraine points out, «the analysis of a new society supposes a renovation of the same analysis». This it is the fundamental challenge for our discipline. In the present text I look at some aspects that can contribute to the accomplishment of this task, especially from the analysis of the José Carlos Mariátegui perspective, the Immanuel Wallerstein modern system-world theory and the Aníbal Quijano coloniality of power concept.